Peran Kompleksitas Tugas Dalam Hubungan Kompetensi, Independensi, Dan Etika Pemeriksa Pajak Dengan Kualitas Hasil Pemeriksaan - Susi Dwi Mulyani; Triwahyudi Heru Purnomo (Esensi: Jurnal Bisnis dan Manajemen, 2019)
The objective of this study empirically analyzes the influence of Competence, Independence, and Tax Auditor Ethic to Tax Audit Quality with Task Complexity as Moderating Variable. This research uses primary data. The population of respondends in this research is tax auditors who worked on Madya Tax Office in Region of Jakarta with minimal work experience is one year. Primary data collection method used is questionnaire method. The data are analyzed by Moderated Regression. The results show that Independence and Tax Auditor Ethic have a positive impact on the Tax Audit Quality while Competence and Task Complexity have no impact on the Tax Audit Quality. The results also show that Task Complexity can weaken the influence of Independence on the Tax Audit Quality but Task Complexity cannot moderate the influence Competence and Tax Auditor Ethic on the Tax Audit Quality.